The Influence of The Picture and Picture Learning Model Oriented towards Character Education on the Motivation and Learning Outcomes of Social Sciences for Fifth Grade Students - Nurul Asmi; Nursalam Nursalam; Muhlis Madani (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine the effect of using the Picture And Picture learning model on the motivation and learning outcomes of Social Sciences for fifth grade students at SD Negeri Kaluku Bodoa, Tallo subdistrict, Makassar city. This research is quantitative research using quasi-experimental methods. The design used in this research was a nonquivalent control group design. The sampling technique uses saturated samples. The number of samples in this study was 50 people, consisting of 25 people in the experimental class and 25 people in the control class. The data collection methods used are questionnaires to measure learning motivation and test sheets to measure student learning outcomes. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis, and at the prerequisite data testing stage, data normality tests and data homogeneity tests are carried out. Meanwhile, to test the hypothesis, the Manova Test is carried out. The research results obtained are 1) there is an influence on learning motivation through the Picture And Picture learning model oriented towards character education in the Social Sciences subject for fifth grade students at SD Negeri Kaluku Bodoa 2) There is an influence on learning outcomes through the Picture And Picture learning model oriented towards character education on the eyes Social Sciences students, fifth grade students at SD Negeri Kaluku Bodoa; 3). The Picture And Picture learning model oriented towards character education on students' motivation and learning outcomes with a significance value of <0.001 <0.05, there is an influence of the Picture And Picture learning model oriented towards character education on the motivation and learning outcomes of class V Social Sciences at SD Negeri Kaluku Bodoa, Tallo Kota District Makassar. So it can be concluded that the Picture and Picture learning model can influence the motivation and learning outcomes of Social Sciences for fifth grade students at SD Negeri Kaluku, Tallo District, Makassar City.